Diseño e implementación de una infraestructura de red para el sector centro suroeste y red redundante para el sector centro norte con tecnología ethernet sobre fibra óptica para la empresa M&E Telecom de la ciudad de Machala - Macanchí Procel, Ivanova Elizabeth (2014)
This project's main objective expedite and optimize the quality of service provided by M & E TELCOM, the city of Machala that is to provide internet quickly and without interruption to achieve it will be designed and set up an infrastructure for improved network fiber optic cabling is the most advanced internet system based on the three-layer model CISCO also be implemented redundancy in north central sector, which already has a fiber optic link.